Electromechanical actuation of CNT/PVDF composite films based on a bridge configuration - 谷孝刚 夏小刚 张楠 肖卓建 范庆霞 杨丰 肖仕奇 陈辉亮 周维亚 解思深 (Chinese physics B, 2017)
Bridged strips consisting of carbon nanotubes and poly（vinylidene fluoride） are developed, which exhibit notable deflection in response to very low driven voltages（ 1 V）, because of both the excellent conductivity of the unique carbon nanotube film and the powerful thermal expansion capability of the polymer. The actuators demonstrate periodic vibrations motivated by the alternating signals. The amplitude of displacement is dependent not only on the driven voltage but also on the applied frequency. The mechanism of actuation is confirmed to be the thermal power induced by the electrical heating. By accelerating the dissipation of heat, the vibration response at higher frequencies can be significantly enhanced.The useful locomotion shows great promise in potential applications such as miniature smart devices and micro power generators.